Penyuluhan Literasi Digital untuk Kelompok Remaja di Yayasan Al Kamilah Desa Serua, Bojongsari Depok - Nurfarah Nidatya; Mansur Juned; Shanti Darmastuti; Dini Putri Saraswati (CV. Multi Kreasi Media, 2025)
The rapid development of digital technology has brought significant changes in the way teenagers access information, communicate, and build their social identity. However, the high intensity of internet use is not always matched by adequate digital literacy skills, making teenagers vulnerable to various risks such as the spread of hoaxes, misuse of social media, violations of digital ethics, and low critical thinking skills. This digital literacy outreach activity aims to improve the understanding and skills of teenagers at the Al Kamilah Foundation in Serua Village, Bojongsari, Depok, in using digital technology intelligently, critically, and responsibly. The methods used include interactive material delivery, group discussions, and simple simulations related to digital information evaluation, media ethics, and the use of technology for self-development and learning. The results of the activity showed an increase in participants' understanding of the concept of digital literacy, awareness of the importance of digital ethics, and initial ability to assess the credibility of information in digital media. This activity is expected to be the first step in building a sustainable digital literacy culture among teenagers, particularly in supporting lifelong learning and readiness to face the challenges of a digital society.